Rainfall and nitrogen addition have no synergistic effects on steppe composition and production in postgrazing succession - Xin, Yue; Huang, Qiuxian; Liu, Biyao; Li, Zixin; Sun, Yurong; Zhang, Min; Yu, Hongwei (Frontiers in Plant Science, 2025)
Most steppes are experiencing postgrazing succession, coupled with rainfall change and nitrogen (N) deposition. Despite the importance of soil resources in shaping community multifunctionality, little is known about how rainfall increase and N deposition influence steppe composition and production during postgrazing succession. We performed a field factorial experiment, subject to rainfall and N, each with three levels, to understand how simulated rainfall increase and N deposition affect the composition and production of a Leymus chinensis steppe. At the low rainfall increase, the dominance of L. chinensis increased with increasing N, while aboveground community production remained unchanged along the N gradient. At the high rainfall increase, aboveground community production was enhanced due to low N addition, but this facilitation disappeared in the presence of high N addition, and L. chinensis dominance was no longer affected by N. N-induced soil eutrophication but not soil acidification and soil microbes strongly affected steppe composition and production. Our findings suggest that high rainfall increase might weaken the potential of N addition to contribute to steppe composition and production, and also highlight the necessity of investigating interactions among multiple global change drivers.